Prevalence of phantom sensations and its relation to smartphone use among medical students of a tertiary care centre in Central India: a cross-sectional study - Padyal, Pratik; Bhelkar, Sandeep; Narlawar, Uday; Jain, Mudita; Kumar, Mohit (International Journal Of Community Medicine And Public Health, 2025)
Background: Phantom sensations, such as phantom vibration (PV) and phantom ringing (PR), are perceptual phenomena where individuals feel their smartphone vibrating or ringing when it is not. These sensations are becoming increasingly common in the digital age, particularly among smartphone users. Due to their intensive use of smartphones for academic and social purposes, medical students may be at higher risk of experiencing these sensations. This study aims to assess the prevalence of phantom sensations and explore its relation to smartphone use among medical students in a tertiary care center in Central India. Methods: A cross-sectional study was conducted among 370 medical students from a tertiary care center in Central India. Data were collected using a self-administered questionnaire, which included demographic details, patterns of smartphone use, and experiences of phantom sensations. Smartphone addiction was measured using the smartphone addiction scale-short version (SAS-SV). Descriptive statistics and chi-square tests were used to analyze the data. Results: The prevalence of PR and vibration sensations among the participants was 40% and 39.45% respectively. A significant association was found between smartphone addiction and the occurrence of PR and vibration sensations. Conclusions: Phantom sensations are highly prevalent among medical students, and their frequency is significantly associated with increased smartphone use. Awareness and interventions may be necessary to reduce excessive smartphone use and manage phantom sensations among medical students.